2018
DOI: 10.1016/j.jns.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity and cognitive processing speed in multiple sclerosis: A systematic review

Abstract: Despite the observed trends, no definite conclusions can be drawn on the relationship between brain connectivity and PS decline in MS given the limitations of the current literature. Future investigations may benefit from theoretical and methodological advances to clarify how MS-related brain damage affects patients' cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 79 publications
(230 reference statements)
3
21
1
2
Order By: Relevance
“…Previous studies have shown regional damage of the dorsolateral prefrontal circuit is detectable in people with MS with information processing speed deficits, including the atrophy of DLPFC, caudate or thalamus (Batista et al, 2012;Nocentini et al, 2014), and our results confirm this association. Additionally, we found a relationship between PASAT-3 performance and RD in the WMT linking the DLPFC to the caudate which is in line with previous systematic reviews identifying relationships between frontal white matter integrity and cognition in MS (Manca et al, 2018;Welton, Kent, Constantinescu, Auer, & Dineen, 2015). We chose RD as the DTI metric to reflect microstructural damage because it has been reported to be an index of demyelination (Song et al, 2005) and it has been shown that RD may be the most sensitive of the DTI-derived metrics when estimating microstructural damage in MS (Lipp et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown regional damage of the dorsolateral prefrontal circuit is detectable in people with MS with information processing speed deficits, including the atrophy of DLPFC, caudate or thalamus (Batista et al, 2012;Nocentini et al, 2014), and our results confirm this association. Additionally, we found a relationship between PASAT-3 performance and RD in the WMT linking the DLPFC to the caudate which is in line with previous systematic reviews identifying relationships between frontal white matter integrity and cognition in MS (Manca et al, 2018;Welton, Kent, Constantinescu, Auer, & Dineen, 2015). We chose RD as the DTI metric to reflect microstructural damage because it has been reported to be an index of demyelination (Song et al, 2005) and it has been shown that RD may be the most sensitive of the DTI-derived metrics when estimating microstructural damage in MS (Lipp et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive dysfunction affects ~40–70% of people with multiple sclerosis (MS), and adversely impacts employment, daily living, social interaction and potential to benefit from rehabilitation (Achiron et al, 2013; Chiaravalloti & DeLuca, 2008; Grzegorski & Losy, 2017; Hamalainen & Rosti‐Otajarvi, 2016). Across the various clinical courses of MS, deficits in processing speed, working memory and sustained attention are found (Drew, Starkey, & Isler, 2009; Manca, Sharrack, Paling, Wilkinson, & Venneri, 2018). These aspects of cognitive dysfunction are critical in many aspects of daily life.…”
Section: Introductionmentioning
confidence: 99%
“…It is detected in 41% MS patients, of which 28% experience significant decline in 5 years [4]. Deficit in processing speed [5] and memory [6, 7] are the most common cognitive impairment in MS and more prevalent in progressive type than relapsing-remitting MS (RRMS) [8]. However, the deficit can also be detected in the early onset of MS (clinically isolated syndrome, CIS) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in neuroimaging studies have highlighted how demyelinating lesions are increasingly detected in grey matter (GM) [18,19], and the association between regional GM loss and functional disability has become a well-established feature of MS [20]. However, the structural neural correlates of specific cognitive symptoms commonly observed in MS have not been completely clarified especially in the progressive phenotypes of this disease [21].…”
Section: Introductionmentioning
confidence: 99%